Glucose metabolism status modifies the relationship between lipoprotein(a) and carotid plaques in individuals with fatty liver disease - Wang, Jiaxuan; Sun, Honglin; Wang, Ying; An, Yu; Liu, Jia; Wang, Guang (Frontiers in Endocrinology, 2022)
Background and aims: Glucose and lipoprotein(a) [Lp(a)] have been recognized risk factors for atherosclerosis. The impact of both factors on fatty liver patients has not been studied. The aim of this study is to explore the role of high-level Lp(a) and different glucose metabolism statuses on carotid plaques in fatty liver patients. Methods: We selected 4,335 fatty liver patients in this cross-sectional study. The diagnosis of fatty liver disease and carotid plaques was made by ultrasound. Participants were divided into four groups based on glucose metabolism status (normal glucose regulation [NGR], lower bound of impaired fasting glucose [IFG-L], higher bound of impaired fasting glucose [IFG-H], diabetes mellitus [DM]) and then categorized into 12 subgroups according to Lp(a) concentrations. The association between variables was estimated by odds ratio (OR). Results: Carotid plaques were present in 1,613 (37.2%) fatty liver patients. Lp(a)≥30 mg/dL was associated with high risk of carotid plaques in those patients with IFG-L, IFG-H and DM (OR 1.934 [95% CI 1.033-3.618], 2.667 [1.378-5.162], 4.000 [2.219-7.210], respectively; p<0.05). Fatty liver patients with DM plus Lp(a)＜10 mg/dL and 10≤Lp(a)＜30 mg/dL were more vulnerable to carotid plaques (OR 1.563 [95% CI 1.090-2.241], 1.930 [1.279-2.914]) , respectively, p＜0.05). Conclusions: Our study first suggested that high-level Lp(a) may raise the risk of carotid plaques in fatty liver patients with not only diabetes but also IFG, manifesting that Lp(a) may be helpful for the early discovery of subclinical atherosclerosis in fatty liver patients with impaired glucose metabolism.